- #1

- 115

- 0

$$\sum_{k=1}^nk^m=\frac{1}{m+1}\sum_{k=0}^{m}\binom{m+1}{k}B_k\;n^{m-k+1}$$

where ##B_k## denotes the kth Bernoulli number.

- Thread starter eddybob123
- Start date

- #1

- 115

- 0

$$\sum_{k=1}^nk^m=\frac{1}{m+1}\sum_{k=0}^{m}\binom{m+1}{k}B_k\;n^{m-k+1}$$

where ##B_k## denotes the kth Bernoulli number.

- #2

- #3

- 115

- 0

So the formula in my first post is correct?

- Last Post

- Replies
- 1

- Views
- 3K

- Last Post

- Replies
- 6

- Views
- 1K

- Last Post

- Replies
- 1

- Views
- 496

- Last Post

- Replies
- 5

- Views
- 2K

- Last Post

- Replies
- 2

- Views
- 2K

- Last Post

- Replies
- 1

- Views
- 740

- Last Post

- Replies
- 2

- Views
- 1K

- Last Post

- Replies
- 1

- Views
- 999

- Last Post

- Replies
- 3

- Views
- 3K

- Last Post

- Replies
- 5

- Views
- 729